Barreiras, facilitadores e motivação para a prática recreacional do tênis de campo na cidade de Uruguaiana – RS - Sanchotene, Ismael Jung (2019)
The study sought to identify the motivational factors, barriers and perceived facilitators for the practice of field tennis in adult recreational practitioners (PRT) of Uruguaiana RS, and to compare this information according to age, sex, and PRT of a private club, PRT of a public space and non-practitioners (NP) of the sport. 144 individuals (76 PRT and 68 NP) with an average age of 38.5 years participated. For the motivation analysis, the motivation inventory was the regular practice of physical and sports activities (IMPRAF-54) adapted to the characteristics of the present study. To identify perceived barriers to the practice of tennis used the questionnaire prepared by Hirayama. Sociodemographic indicators, body mass index and physical activity level were used to characterize the participants. Exploratory data analysis was performed identifying the normality of distributions between numerical variables, which were described using the mean and standard deviation, while categorical variables were described with absolute and relative frequencies. Comparisons of the scores of the different motivational factors and perceived barriers between the sexes, private club PRT, public space PRT and NP were performed using the independent samples t-test and one-way ANOVA, respectively. Pearson's correlation was used to identify possible relationships between motivational factors and perceived barriers scores and age. Health was the main motivational factor in the whole sample (PRT and NP) and also in the analyzes according to subgroups (gender, age, private club PRT, public space PRT and NP). The most important perceived barrier to recreational tennis practice by study participants was “lack of time”.